Optimization of convergent angle of the Venturi meter for best coefficient of discharge. Issue 12 (10th November 2022) - Khan, Zohaib Ahmed; Jain, Naman
Abstract: Computational fluid dynamics is a compelling apparatus for getting stream flow and anticipating how this flow will react to various limiting boundary conditions. With this learning, the focal point of this research is applying computational fluid elements such as CFD to issues dealing with stream flow measurement/estimation in closed conduits such as pipes utilizing differential stream meters like the Venturi meter. After thorough research from the existing literature, it was determined that the convergent angle (CA) of a standard Venturi meter has not been optimized yet. The range given for a standard ASME Venturi CA is 20–22°. More than 50 models were created and run in ANSYS FLUENT, which was used as a CFD tool. Three β -ratios are taken into consideration here, which are 0.4, 0.5 and 0.6. An optimum value of CA, corresponding to each β, is obtained by finding out the best coefficient of discharge (closest to 0.99) for each test value of CA. Another aspect explored in this research is the relationship between Reynolds number and coefficient of discharge. This is done with the integration of ANSYS FLUENT and laboratory results. The results of this study yield a definite value of CA for each β . HIGHLIGHTS: The focal point of this research is the optimization of the convergent angle of the Venturi meter. More than 50 models were created and run in ANSYS FLUENT, and three β-ratios are taken into consideration here, which are 0.4, 0.5 and 0.6. An optimum value of convergent angle, corresponding to each β, is obtained by finding out the best coefficient of discharge (closest to 0.99) for each test value of convergent angle. Graphical Abstract